A New Era of Armed Conflict: The Role of State and Non-State Actors in Cyber Warfare with Special Reference to Russia-Ukraine War - Khalil Ahmad; Bitar Mohammad; Anandha Krishna Raj S. (TalTech Journal of European Studies)
The use of cyber operations in armed conflicts has become a reality, with several states openly admitting to being involved in such activities. An increasing number of nations are developing military cyber capabilities, and the use of these operations is expected to rise. Advancements in offensive cyber capabilities have demonstrated that these operations can significantly impact civilian infrastructure and cause harm to humans. This study explores the complex application of international humanitarian law (IHL) to cyber warfare, focusing on the evolving roles of both state and non-state actors. It examines the difficulties in distinguishing between combatants and non-combatants in the light of the concept of direct participation in hostilities during cyberattacks. Furthermore, this paper examines the responsibilities and legal consequences for states that direct or control non-state actors and the need to adapt IHL to the specific nature of cyber conflicts. It underscores the crucial need for strong legal frameworks to protect civilians and uphold humanitarian principles in the digital era. This study employs cyberattacks which occurred during the Russian-Ukraine armed conflict as a case study.